Internalisasi Nilai-Nilai Keislaman melalui Project Based Learning (PjBL) pada Anak Berkebutuhan Khusus: Studi Kualitatif di Sekolah Luar Biasa - Abdul Basith; Indriana Rahmawati (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
This research aims to analyse the internalisation of Islamic values through project-based learning for children with special needs in Special Schools (SLB). The research uses a qualitative approach with a multi-case study design conducted at SLBN Kutai Timur, SLBN Penajam Paser Utara, and SLBN Berau, East Kalimantan. The research subjects consisted of the school principal, the vice principal in charge of the curriculum, the coordinator of the Pancasila Student Profile Strengthening Project (P5), supporting teachers, and related parties involved in the project implementation. Data were collected through interviews, observations, and documentation, and then analysed using the Miles, Huberman, and SaldaÃ±a model, which includes data condensation, data presentation, and conclusion drawing. Data analysis was reinforced with the help of NVivo software. The research results show that project-based learning is an effective means of internalising Islamic values in special needs students through real and contextual learning experiences. The internalised values include ta'awun (helping each other), ukhuwah (brotherhood), amanah (responsibility), ihsan (doing good), gratitude, deliberation, and khalifah fil ardh (concern for the environment). These values are realised through activities such as waste management, making traditional regional foods, traditional games, entrepreneurship market day, and democratic voting. The process of internalisation is supported by collaboration between schools, teachers, parents, and the community. Research findings indicate that project-based learning not only develops academic and vocational skills but also strengthens the religious character of special needs students in an inclusive and contextual manner.